Nanoemulsion-enhanced insecticidal activity of Cymbopogon citratus and Mentha longifolia essential oils against the red flour beetle (Tribolium castaneum) - Jasman, Ammar K.; Slomy, Ali K.; Khaleel, Ayad Ismael (Elsevier, 2025)
This study evaluated the insecticidal activity of essential oils (EOs) from Cymbopogon citratus and Mentha longifolia, along with their respective nanoemulsions, against Tribolium castaneum, a major pest of stored food products worldwide. GC-MS analysis of hydrodistilled EOs revealed pulegone (32.7 %) and menthone (18.5 %) as major constituents in M. longifolia, whereas C. citratus contained geranial (42.6 %) and neral (31.5 %) as dominant compounds. Nanoemulsions were prepared via ultrasonication to yield stable formulations with mean droplet sizes of 78.3 ± 3.2 nm for M. longifolia (MLNE) and 82.7 ± 4.1 nm for C. citratus (CCNE). Their insecticidal potential was assessed using contact toxicity, fumigant toxicity, and feeding deterrence bioassays. After 72 h of exposure, LC50 values for contact toxicity were 2.43 μL/cm2 (MLEO), 1.68 μL/cm2 (MLNE), 2.87 μL/cm2 (CCEO), and 2.05 μL/cm2 (CCNE). Fumigant LC50 values were 21.8, 14.3, 25.6, and 17.9 μL/L air for MLEO, MLNE, CCEO, and CCNE, respectively. MLNE demonstrated the highest toxicity, while CCNE exhibited the strongest feeding deterrent effect. Nanoemulsion formulations enhanced biological efficacy by approximately 40–45 %, likely due to improved penetration through the insect cuticle and increased surface area. These findings suggest that nanoemulsions of M. longifolia and C. citratus EOs may offer an effective, eco-friendly alternative to conventional pesticides for managing stored product pests.